STUDENTS’ LISTENING STRATEGIES TO COPE WITH THE PROBLEMS IN LISTENING CLASS - Sofia Idawati Lubis; Dinda Suri; Isnania Ardhana (FKIP Universitas Al Washliyah Medan, 2021)
This study aims to reveal the strategies employed by the students in listening class. Listening is one skill that highly complicated, started from receiving, understanding, remembering, evaluating, and responding to what they hear. It becomes a problem to the students especially in an EFL classroom. Sometimes the students are discouraged to this situation. To overcome the problems, one of the solutions is employing the strategies of listening. The research subject were the students of first semester who take Listening for General Communication subject. Data were collected by questionnaire It consisted of 24 questions for metacognitive strategy, cognitive strategy, and socio-affective strategy. It adapted from Listening Comprehension Strategy Inventory (LCSI). The results showed that metacognitive strategy (50,4%) was the most strategy frequently employed by the students. The second strategy was cognitive strategies (33,0%), and the last was socio-affective strategies (16,6%).